The Tradition of Maantaan Nasi Jujuang ot The Wedding Ceremony In Jorong Tanjuang Balik Nagari Salimpek Sub-District Gumanti Solok Regency - Arda, Afrillia Marda Tillah; Selvi Kasman; Hijratur Rahmi (Kirana Publisher (KNPub), 2023)
The research entitled ”The tradition of Maantaan Nasi Jujuang at the wedding ceremony in jorong Tanjuang Balik Nagari Salimpek, Lembah Gumanti District, Solok Regency ainms to describe the form of the procession maantaan nasi jujuang and the symbolic meaning contained in the juadah (delivery) in the procession maantan nasi jujuang at a wedding ceremony the theory used in this research is symbolic interpretive the theory by Clifford Geertz on Dolgin et al. The method that the author uses is a qualitative method with data collection techniques, namely observation, interviews, and documentation. The results of the study found that the wedding ceremony was carried out with the stages of the wedding procession, namely maresek, mancaliak jerek (membuat kesepakatan), maantaan siriah, manduduak mamak, batak tando (batimbang tando), manjapuik marapulai,baralek dan maantaan anak. The maantaan nasi jujuang procession is a form of hospitality from the anak daro and family to the marapulai family with the aim of strengthening the relationship between the two parties. The procession has three stages, namely the tangah jalan field (arakan),the tangah countryard field (speech), the tangah field of the house (eating together). In addition, there meaning in the juadah (delivery) a dulang siriah , the kamaloyang , pinyaram , ampiang , buah kubang (godok-godok) , barek nan sasukek , nasi kunik , paruik-paruik ayam.